Evaluasi terhadap Peraturan Bersama Menteri Tahun 2006 tentang Pendirian Rumah Ibadah - Binsar Antoni Hutabarat (Reformed Center for Religion and Society, 2017)
ABSTRACT:Â This article with a title Evaluation to the Joint Regulation of Ministers in 2006 about the Establishment of a House of Worship will focus on the evaluation of the formulation of the Joint Regulation of Ministers in 2006 about the Establishment of a House of Worship (Peraturan Bersama Menteri PBM), as well as the evaluation of the application and impact of the enacted regulation. The research methodology uses qualitative research with an in-depth interview to some church leaders in Bekasi, West Java, who are directly connected with the enactment of this regulation, and also research to the related documents with the PBM, especially the policy wich founded the PBM. The research finding is the formulation of the Joint Regulation of Ministers about the Establishment of a House of Worship has not yet fitted with the formulation policy model of a democratic country so that its application is not in accordance with the expected goal. PBM application gives negative impact to the inter-religious harmony in Indonesia. KEYWORDS: regulation of the esthablisment of a house of worship, freedom of worship, policy evaluation